Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1016/j.ijcard.2013.04.137
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac autonomic control in Brugada syndrome patients during sleep: The effects of sleep disordered breathing

Abstract: Aims Brugada syndrome is characterized by typical ECG features, ventricular arrhythmias and sudden cardiac death (SCD), more frequent during nighttime. Autonomic cardiovascular control has been implicated in triggering the ventricular arrhythmias. Sleep-disordered breathing (SDB) elicits marked autonomic changes during sleep and it is associated with an increased risk of nighttime SCD. Brugada patients may have a higher likelihood of SDB compared to controls. However, no data are available on cardiac autonomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…Experimental and clinical studies have established that derangement of the autonomic nervous system may play a key role in the pathophysiology of the cardiovascular consequences that occur in patients with acute and chronic SCI. During sleep, in normal subjects, autonomic cardiac control is highly dynamic and active, with a predominant vagal modulation during NREM sleep and a shift of sympatho-vagal balance towards sympathetic predominance during REM sleep [Trinder et al 2001; Crasset et al 2001; Beharav et al 1995; Busek et al 2005; Tobaldini et al 2013]. However, no studies have so far investigated the autonomic cardiac changes during sleep in SCI patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental and clinical studies have established that derangement of the autonomic nervous system may play a key role in the pathophysiology of the cardiovascular consequences that occur in patients with acute and chronic SCI. During sleep, in normal subjects, autonomic cardiac control is highly dynamic and active, with a predominant vagal modulation during NREM sleep and a shift of sympatho-vagal balance towards sympathetic predominance during REM sleep [Trinder et al 2001; Crasset et al 2001; Beharav et al 1995; Busek et al 2005; Tobaldini et al 2013]. However, no studies have so far investigated the autonomic cardiac changes during sleep in SCI patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, new non-linear methods, such as symbolic dynamics and entropy-derived measures, have been proposed as valid tools able to overcome important technical limitation of spectral analysis and capable of providing complementary information on the neural mechanisms which control and regulate cardiac sinus node function [Tobaldini et al 2009; Tobaldini et al 2013; Viola et al 2011; Porta et al 2007; Porta et al 2007]. …”
Section: Introductionmentioning
confidence: 99%
“…For this reason, cardiovascular autonomic assessment in severe OSA patients can importantly be affected by non-neural oscillations related to the continuous episodes of apnea which could thereby alter HRV analysis (Wang et al, 2008); this factor must be taken into account when analyzing PSG data and interpreting the results. To this regard, in a recent paper assessing HRV during sleep in patients with Brugada syndrome diagnosed with or without SDB, ECG recordings derived from polysomnographic studies were analyzed, carefully avoiding periods with apneas/hypopneas and considering only ECG segments associated with stable and regular breathing (Tobaldini et al, 2013). This approach allowed the observation that Brugada syndrome, a rare but life- threatening disease characterized by ventricular arrhythmias and sudden cardiac death, more frequent during nighttime, was associated with an impaired autonomic cardiovascular control in the presence of comorbid SDB (Tobaldini et al, 2013).…”
Section: Hrv and Sleep Disordersmentioning
confidence: 99%
“…To this regard, in a recent paper assessing HRV during sleep in patients with Brugada syndrome diagnosed with or without SDB, ECG recordings derived from polysomnographic studies were analyzed, carefully avoiding periods with apneas/hypopneas and considering only ECG segments associated with stable and regular breathing (Tobaldini et al, 2013). This approach allowed the observation that Brugada syndrome, a rare but life- threatening disease characterized by ventricular arrhythmias and sudden cardiac death, more frequent during nighttime, was associated with an impaired autonomic cardiovascular control in the presence of comorbid SDB (Tobaldini et al, 2013). …”
Section: Hrv and Sleep Disordersmentioning
confidence: 99%
“…We have recently shown that these autonomic dynamics may be preserved in pathological conditions, such as in patients affected by Brugada syndrome and in patients with spinal cord injuries (Tobaldini et al. ,c, ).…”
Section: Discussionmentioning
confidence: 99%